2009
DOI: 10.5174/tutfd.2009.01607.1
|View full text |Cite
|
Sign up to set email alerts
|

The Alteration Of Plasma Atrial Natriuretic Peptide Levels Induced By Postural Changes In Archery Athletes

Abstract: Objectives:The aim of this study was to investigate plasma atrial natriuretic peptid levels in sitting and supine positions and cardiac functions in young male archery athletes. Materials and Methods:Six archery athletes and 10 sedentary males volunteered to participate in the study. Venous blood samples were taken after 10 minutes sitting and after 10 minutes in supine position. Plasma ANP levels were measured by the ELISA method. Cardiac parameters were assessed by echocardiography.Results: Plasma ANP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…E1 = Exercised group, NE1 = nonexercised group, ∆ K-ANP1 = changes from K to ANP1, ∆ K-ANP2 = changes from K to ANP2, ∆ K-R1 = changes from K to R1, ∆ K-R2 = changes from K to R2, ∆ K-R3 = changes from K to R3. untrained healthy controls (14). It was shown that an increase in plasma ANP concentrations in healthy subjects may eliminate intermittent overhydration and may participate in the regulation of diuresis and natriuresis resulting from postural changes (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E1 = Exercised group, NE1 = nonexercised group, ∆ K-ANP1 = changes from K to ANP1, ∆ K-ANP2 = changes from K to ANP2, ∆ K-R1 = changes from K to R1, ∆ K-R2 = changes from K to R2, ∆ K-R3 = changes from K to R3. untrained healthy controls (14). It was shown that an increase in plasma ANP concentrations in healthy subjects may eliminate intermittent overhydration and may participate in the regulation of diuresis and natriuresis resulting from postural changes (6).…”
Section: Discussionmentioning
confidence: 99%
“…E1 = Exercised group, NE1 = nonexercised group, K = baseline measurement, ANP1 = measurement made after 5 min of atrial natriuretic peptide administration, ANP2 = measurement made after 15 min of atrial natriuretic peptide administration, R1 = measurement made after 1 min of reperfusion period, R2 = measurement made after 15 min of reperfusion period, R3 = measurement made after 30 min of reperfusion period. untrained healthy controls (14). It was shown that an increase in plasma ANP concentrations in healthy subjects may eliminate intermittent overhydration and may participate in the regulation of diuresis and natriuresis resulting from postural changes (6).…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce yapılan çalışmalar sağlıklı kişilerde plazma ANP düze-yinin egzersize bağlı arttığını göstermiştir (6,7). Ayrıca, düzenli spor yapan kişilerde ANP düzeylerinin artış gös-terdiği daha önce yapılan çalışmalarda bildirilmiştir (8,9). Egzersiz belki de ANP artışına yol açan bir faktör olarak, iskemi sonrasındaki reperfüzyon döneminde koruyucu etkiler meydana getirebilir.…”
Section: Müştürunclassified